1 Records of the Colony of Rhode Island and Providence Plantations, in New England 94 (John Russell Bartlett ed., 1856) - (:unkn) unknown (My University, 1639)
Ordered that "no man" shall go two miles from town unarmed. Also ordered that none shall come to any public meeting without his weapon. Penalty of five shillings per violation.
Keywords: REQUIRED POSSESSION